2018
DOI: 10.1177/0018578718779005
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Opioid Medication Stewardship Practices at Academic Medical Centers

Abstract: The results of a survey of academic medical centers assessing the presence and description of opioid stewardship activities. Methods: Academic medical centers within the Vizient University Health System Consortium Pharmacy Network were asked to complete a survey related to opioid stewardship activities. The survey consisted of 30 questions aimed at identifying current opioid stewardship practices among hospitals and health systems. Results: There were 27 respondents to the survey. Only 42.3% of respondents hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
(5 reference statements)
1
13
0
Order By: Relevance
“…Prescriber education and guidelines have been shown to successfully reduce the number of opioids initially prescribed by more than half [ 13 ]. This study showed that more than half of the respondents stated that their hospital did not have a policy for prescriber education, which was similar to a study conducted in the US where only 26.9% of hospitals responded having a policy that requires education of providers and/or caregivers about safe opioid prescribing [ 14 ]. Education of prescribers has been reported in Australia and New Zealand as one of the main opioid stewardship measures (78%) currently implemented.…”
Section: Discussionsupporting
confidence: 73%
“…Prescriber education and guidelines have been shown to successfully reduce the number of opioids initially prescribed by more than half [ 13 ]. This study showed that more than half of the respondents stated that their hospital did not have a policy for prescriber education, which was similar to a study conducted in the US where only 26.9% of hospitals responded having a policy that requires education of providers and/or caregivers about safe opioid prescribing [ 14 ]. Education of prescribers has been reported in Australia and New Zealand as one of the main opioid stewardship measures (78%) currently implemented.…”
Section: Discussionsupporting
confidence: 73%
“…The ‘deprescribing’ of opioids needs to address reducing the initial prescription of opioids, but also how to support the cessation of opioids whilst still providing access to appropriate pain management. Opioid mitigation strategies have begun, for example, national initiatives , opioid stewardship programmes and up‐scheduling of codeine in Australia and Italy . However, research on opioid mitigation strategies specific to the needs of patients with chronic noncancer pain is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Some institutions have implemented opioid stewardship programs (OSPs) to achieve these goals. Core pillars of OSPs include interprofessional collaboration on protocols and services related to multimodal pain management, education on opioid prescribing and stewardship to staff and providers, education to patients, caregivers and community members on safe opioid use and disposal, opioid-related risk reduction, and data analysis and reporting of related quality metrics [ 38 , 66 , 68 , 519 , 520 , 521 , 522 ]. An expert panel has proposed quality indicators for measuring opioid stewardship interventions in hospital and emergency settings.…”
Section: Interprofessional Collaboration In Sustaining Perioperatimentioning
confidence: 99%